Influence of size and taper of basic root canal preparation on root canal cleanliness: A scanning electron microscopy study - Plotino, Gianluca; Özyürek, Taha; Grande, Nicola Maria; Gündoğar, Mustafa (Wiley, 2019)
Aim To investigate whether a minimally invasive basic root canal preparation technique has an influence on root canal cleanliness in extracted mandibular molar teeth. Methodology A total of 80 root canals (40 mesiobuccal and 40 mesio-lingual) from 40 mandibular molars were included. The teeth were divided equally into four different experimental groups depending on the subsequently root canal preparation technique: Group 1: a basic preparation was performed up to size 20,.04 taper; Group 2: a basic preparation was performed up to size 2,.06 taper; Group 3: a basic preparation was performed up to size 25,.04 taper; and Group 4: a basic preparation was performed up to size 25,.06 taper. After the use of each instrument, each root canal was irrigated with 2.5 mL of 6% sodium hypochlorite for 30 s. Then, 1 mL NaOCl was activated for 20 s using an EDDY sonic tip. Final irrigation was performed using a total of 5 mL of 17% EDTA solution. The roots were then split longitudinally and all root canal thirds were observed through scanning electron microscopy (SEM) to evaluate the presence of superficial debris and smear layer using a scoring system. Data were statistically analysed using the Kruskal-Wallis and Bonferroni tests with a level of significance set at P < 0.05. Results In all groups, there was significantly more residual debris and smear layer in the apical third (P < 0.05), with no differences between the middle and coronal thirds (P > 0.05). For both the parameters analysed, there was no difference amongst the groups in the middle and coronal thirds (P > 0.05), whilst in the apical third significantly less debris and smear layer was found in specimens from groups 3 and 4 than for groups 1 and 2 (P < 0.05). Conclusion All basic root canal preparation techniques were associated with less debris and smear layer on the canal walls in the middle and coronal thirds, without differences among them. Even though debris and smear layer were always present in the apical third, an apical size of 25 resulted in significantly cleaner canals walls compared to a size 20.
WOS: 000459616900010
PubMed ID: 30129186
Keywords: Debris; EDDY; Mandibular Molar; Root Canal Preparation; Smear Layer